Y - y1 = m(x - x1)
slope(m) = -4/3
(0,-12)....x1 = 0 and y1 = -12
sub
y - (-12) = -4/3(x - 0) =
y + 12 = -4/3(x - 0) <=== point slope form
y + 12 = -4/3x
y = -4/3x - 12 <=== slope intercept form
y = -4/3x - 12
4/3x + y = -12
4x + 3y = -36 <=== standard form
Answer:
Step-by-step explanation:
You will be more likely to eat one with caramel
Answer:6
Step-by-step explanation:
Answer:
$10
Step-by-step explanation:
divide $4 by 8. you get $.50. multiply that by 20 and you get $10
Answer:
C
Step-by-step explanation: